A method for preparing a fire-resistant double-layer fiber composite aerogel felt

CN116789435BActive Publication Date: 2026-10-30CHINA UNIV OF MINING & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310813616.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2026-10-30
Estimated Expiration
2043-07-04

AI Technical Summary

Technical Problem

玄武岩纤维拥有着优异的力学性能,较强的耐酸碱性,优良的隔热能力以及较低的价格,但是其在高温火焰的冲击下容易发生脆化从而导致纤维毡性能的急速下降

Benefits of technology

[0027]本发明使用双硅源制备具有较强力学性能、较低密度和优异隔热能力的气凝胶,并与高硅氧纤维进行复合制备高硅氧纤维气凝胶毡,最后通过缝纫工艺将其与玄武岩纤维毡进行复合制备出双层纤维复合气凝胶毡,测试其室温热导率,室温力学性能和火场下的隔热能力。结果表明该双层纤维复合气凝胶毡在隔热与力学性能等方面表现优异。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116789435B_ABST
    Figure CN116789435B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of a fire-resistant double-layer fiber composite aerogel felt and relates to the technical field of fire-resistant materials. The application uses double silicon sources to prepare aerogel with strong mechanical properties, low density and excellent heat insulation capacity, and the aerogel is combined with high-silica fiber to prepare high-silica fiber aerogel felt, and finally, the high-silica fiber aerogel felt is combined with basalt fiber felt through a sewing process to prepare the double-layer fiber composite aerogel felt, which is excellent in heat insulation and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fire-resistant materials technology, and in particular to a method for preparing a fire-resistant double-layer fiber composite aerogel felt. Background Technology

[0002] In recent years, with the rapid development of the world economy, the construction of transportation infrastructure has also been advancing rapidly, with the number of long-span bridges, including suspension bridges and cable-stayed bridges, increasing daily. However, about 3% of the large vehicles traveling on bridges are tanker trucks carrying flammable and explosive materials. Accidents involving such vehicles on bridges have a very high probability of causing serious fires. Studies show that fires caused by tanker trucks can raise the temperature to over 1100°C within 10 minutes. Bridge fires can paralyze traffic, and since the main structure of long-span bridges is steel, sustained high temperatures can cause the steel structure to fail, leading to bridge collapse and posing a significant threat to personal safety. Currently, the mainstream fireproof products on the market include fireproof boards, fireproof coatings, and fireproof fiber felt. For the protection of bridge cables, products are required to have low weight, good mechanical properties, and strong thermal insulation capabilities; therefore, fireproof fiber felt has become the first choice for cable protection. There are many types of fireproof fiber felt, including basalt fiber felt, mullite fiber felt, ceramic fiber felt, high silica fiber felt, etc. In recent years, composite aerogel fiber felt has also emerged, among which high silica fiber aerogel felt has better overall performance.

[0003] High-silica fiber aerogel felt is a composite of high-silica fiber felt and aerogel. High-silica fiber is a fiber product obtained by acid extraction and sintering of borosilicate glass fiber, with a SiO2 content exceeding 95%, giving it excellent high-temperature resistance. Aerogel, on the other hand, is a porous material with a three-dimensional network structure, possessing advantages such as high porosity, high specific surface area, and low thermal conductivity. The high-silica aerogel felt prepared by combining these two materials combines the advantages of both, making it an excellent choice for cable fireproofing materials; however, it also suffers from a high price.

[0004] Basalt fiber is a continuous inorganic fiber made from volcanic basalt through drawing. Basalt fiber possesses excellent mechanical properties, strong acid and alkali resistance, excellent heat insulation capabilities, and a relatively low price. However, it is prone to embrittlement under the impact of high-temperature flames, leading to a rapid decline in the performance of the fiber felt.

[0005] Therefore, providing a low-cost fiber felt material with mechanical properties and thermal insulation capabilities that meet fire protection requirements is an urgent technical problem that needs to be solved. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing fire-resistant double-layer fiber composite aerogel felt, so as to solve the problems existing in the prior art, and thus greatly reduce the cost while taking into account the weight, mechanical properties and heat insulation capacity of fire-resistant fiber felt.

[0007] To achieve the above objectives, the present invention provides the following solution:

[0008] This invention provides a double-layer fiber composite aerogel felt, which is composed of basalt fiber felt and high silica fiber aerogel felt;

[0009] The high-silica fiber aerogel felt is made by combining high-silica fibers with aerogel materials; the aerogel materials use tetraethyl orthosilicate and methyltriethoxysilane as dual silicon source precursors.

[0010] The present invention also provides a method for preparing the above-mentioned double-layer fiber composite aerogel felt, comprising the following steps:

[0011] (1) Preparation of sol: Mix silicon source, anhydrous ethanol and water, add activator to the mixture, adjust the pH of the resulting system to between 2 and 3, and obtain the sol;

[0012] (2) Preparation of high silica fiber aerogel felt: The high silica fiber was impregnated with the sol, and then the pH of the system was adjusted to neutral. After aging, drying and treatment, the high silica fiber aerogel felt was obtained.

[0013] (3) Preparation of double-layer fiber composite aerogel felt: The high silica fiber aerogel felt and basalt fiber felt are combined by sewing process to obtain the double-layer fiber composite aerogel felt.

[0014] In this invention, the drying process employs supercritical carbon dioxide drying.

[0015] In this invention, the sewing thread is a glass fiber roving with a linear density of 200-300 tex.

[0016] As a further preferred embodiment of the present invention, in step (1), hydrochloric acid is used to adjust the pH value of the system, and the concentration of hydrochloric acid is preferably 1 mol / L; in step (2), ammonia is used to adjust the pH value of the system, and the concentration of ammonia is preferably 0.5 mol / L.

[0017] As a further preferred embodiment of the present invention, the silicon source is a dual silicon source with a molar ratio of tetraethyl orthosilicate to methyltriethoxysilane of 1:0.8-1.

[0018] As a further preferred embodiment of the present invention, the molar ratio of the silicon source, ethanol and water is 1:15-20:2.

[0019] As a further preferred embodiment of the present invention, the activator is hexadecyltrimethylammonium bromide, and the amount added is 0.3-0.5% of the volume of the mixture.

[0020] As a further preferred embodiment of the present invention, the aging temperature is room temperature, and the aging time is preferably 24 hours; the aging steps are: first aging treatment in a mixture of tetraethyl orthosilicate / ethanol, and then secondary aging treatment in ethanol; the aging temperature for both steps is 60-70°C, and the aging time for both steps is preferably 12 hours.

[0021] As a further preferred embodiment of the present invention, the volume ratio of tetraethyl orthosilicate to ethanol in the tetraethyl orthosilicate / ethanol mixture is 1:5-7.

[0022] As a further preferred embodiment of the present invention, the density of the high-silica fiber aerogel felt is 180-200 kg / m³. 3 The thickness is 3-5mm; the density of the basalt fiber felt is 120-150kg / m³. 3 The thickness is 3-5mm.

[0023] The present invention further provides the application of the above-mentioned double-layer fiber composite aerogel felt as a fire-resistant material.

[0024] This invention prepares high-silica fiber aerogel felt using dual silicon sources. The aerogel product prepared using dual silicon sources has higher skeleton strength, less powder shedding during use, and more stable performance. It is then combined with basalt fiber felt through a sewing process to develop a double-layer fiber composite aerogel felt.

[0025] This invention combines high-silica fiber aerogel felt with basalt fiber felt. When in use, the basalt fiber felt layer is used as the inner layer and the high-silica fiber aerogel felt layer is used as the outer layer. This can avoid direct contact between the basalt fiber felt and the fire site and greatly reduce costs.

[0026] The present invention discloses the following technical effects:

[0027] This invention utilizes a dual silicon source to prepare an aerogel with strong mechanical properties, low density, and excellent thermal insulation capabilities. This aerogel is then composited with high-silica fibers to prepare a high-silica fiber aerogel felt. Finally, it is combined with basalt fiber felt using a sewing process to prepare a double-layer fiber composite aerogel felt. Its room temperature thermal conductivity, room temperature mechanical properties, and thermal insulation capabilities under fire conditions are tested. The results show that this double-layer fiber composite aerogel felt exhibits excellent performance in terms of both thermal insulation and mechanical properties. Attached Figure Description

[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 The temperature change of the cable surface under the protection of the double-layer fiber composite aerogel felt prepared in Example 1 of the present invention;

[0030] Figure 2 The temperature change of the cable surface under the protection of the double-layer fiber composite aerogel felt prepared in Example 2 of the present invention;

[0031] Figure 3 The temperature change of the cable surface under the protection of the double-layer fiber composite aerogel felt prepared in Example 3 of the present invention;

[0032] Figure 4 The temperature change of the cable surface under the protection of the double-layer fiber composite aerogel felt prepared in Comparative Example 1 of this invention.

[0033] Figure 5 The temperature change of the cable surface under the protection of the double-layer fiber composite aerogel felt prepared in Comparative Example 2 of this invention. Detailed Implementation

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0036] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0037] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0038] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0039] Example 1

[0040] A method for preparing a double-layer fiber composite aerogel felt, comprising the following steps:

[0041] (1) Preparation of sol: Silicon source, ethanol and water are placed in a container in a molar ratio of 1:15:2 to obtain a mixture, wherein the silicon source is tetraethyl orthosilicate and methyltriethoxysilane in a molar ratio of 1:0.8; and 5% by volume of hexadecyltrimethylammonium bromide is added as an activator. The mixture is stirred for 10 min to make it uniform, and then 1 mol / L hydrochloric acid is added to adjust the pH value to 2. The mixture is stirred for 30 min to obtain the sol.

[0042] (2) Preparation of high silica fiber aerogel mat: The sol is fully immersed from top to bottom by spraying to achieve a density of 180 kg / m³. 3 A 3mm thick high-silica fiber aerogel felt was prepared by slowly adjusting the pH to 7 with 0.5mol / L ammonia solution. After gelation, it was aged at room temperature for 24 hours, then aged in a 1:7 volume ratio tetraethyl orthosilicate / ethanol mixture for 12 hours, and then aged in ethanol liquid for 12 hours, with the ambient temperature being 60℃. Finally, the wet gel was placed in a pressure vessel, and the air in the vessel was replaced three times with carbon dioxide. Then, carbon dioxide was pumped in until the pressure reached 9.5MPa, and the temperature was raised to 35℃ for 5 hours for supercritical carbon dioxide drying to prepare the high-silica fiber aerogel felt.

[0043] (3) Preparation of composite materials: A composite material with a density of 130 kg / m³ was prepared. 3 The basalt fiber felt with a thickness of 3 mm and the high silica fiber aerogel felt prepared in step (2) are combined by sewing process (using 300 tex glass fiber untwisted yarn) to finally prepare a fire-resistant double-layer aerogel fiber felt composite material.

[0044] The thermal conductivity at room temperature was tested using an HFM436 thermal conductivity analyzer. The material was cut into strips with an effective length and width of 100 mm and 25 mm, respectively. The tensile strength was tested using a universal testing machine. The results showed that the thermal conductivity at room temperature of the double-layer fiber composite aerogel felt was 0.023 W / (m·K), and the tensile strength was 572 N / 25 mm. The tensile strength of the single 3 mm high silica fiber felt before composite was 96 N / 25 mm, and the tensile strength of the 3 mm basalt fiber felt was 121 N / 25 mm.

[0045] Example 2

[0046] A method for preparing a double-layer fiber composite aerogel felt, comprising the following steps:

[0047] (1) Preparation of sol: Silicon source, ethanol and water are placed in a container in a molar ratio of 1:15:2 to obtain a mixture, wherein the silicon source is tetraethyl orthosilicate and methyltriethoxysilane in a molar ratio of 1:0.8, and 5% by volume of hexadecyltrimethylammonium bromide is added as an activator. The mixture is stirred for 10 min to make it uniform, and then 1 mol / L hydrochloric acid is added to adjust the pH value to 3. The mixture is stirred for 30 min to obtain the sol.

[0048] (2) Preparation of high silica fiber aerogel mat: The sol is fully immersed from top to bottom by spraying to achieve a density of 190 kg / m³. 3 A 5mm thick high-silica fiber aerogel felt was prepared by slowly adjusting the pH to 7 with 0.5mol / L ammonia solution. After gelation, it was aged at room temperature for 24 hours, then aged in a 1:7 volume ratio tetraethyl orthosilicate / ethanol mixture for 12 hours, and then aged in ethanol liquid for 12 hours, with the ambient temperature being 60℃. Finally, the wet gel was placed in a pressure vessel, and the air in the vessel was replaced three times with carbon dioxide. Then, carbon dioxide was pumped in until the pressure reached 9.5MPa, and the temperature was raised to 35℃ for 5 hours for supercritical carbon dioxide drying to prepare the high-silica fiber aerogel felt.

[0049] (3) Composite materials: with a density of 150 kg / m³ 3 Basalt fiber felt with a thickness of 5 mm and high silica fiber aerogel felt are combined through a sewing process (using 300 tex glass fiber untwisted yarn) to finally prepare a fire-resistant double-layer aerogel fiber felt composite material.

[0050] The measured thermal conductivity of the double-layer fiber composite aerogel felt at room temperature is 0.029 W / (m·K), the tensile strength is 953 N / 25 mm, the tensile strength of the single 5 mm high silica fiber felt before composite is 128 N / 25 mm, and the tensile strength of the 5 mm basalt fiber felt is 174 N / 25 mm.

[0051] Example 3

[0052] A method for preparing a double-layer fiber composite aerogel felt, comprising the following steps:

[0053] (1) Preparation of sol: Silicon source, ethanol and water are placed in a container in a molar ratio of 1:15:2 to obtain a mixture, wherein the silicon source is tetraethyl orthosilicate and methyltriethoxysilane in a molar ratio of 1:0.8, and 5% by volume of hexadecyltrimethylammonium bromide is added as an activator. The mixture is stirred for 10 min to make it uniform, and then 1 mol / L hydrochloric acid is added to adjust the pH value to 3. The mixture is stirred for 30 min to obtain the sol.

[0054] (2) Preparation of high silica fiber aerogel mat: The sol is fully immersed from top to bottom by spraying to achieve a density of 190 kg / m³. 3 A 5mm thick high-silica fiber aerogel felt was prepared by slowly adjusting the pH to 7 with 0.5mol / L ammonia solution. After gelation, it was aged at room temperature for 24 hours, then aged in a 1:7 volume ratio tetraethyl orthosilicate / ethanol mixture for 12 hours, and then aged in ethanol liquid for 12 hours, with the ambient temperature being 60℃. Finally, the wet gel was placed in a pressure vessel, and the air in the vessel was replaced three times with carbon dioxide. Then, carbon dioxide was pumped in until the pressure reached 9.5MPa, and the temperature was raised to 35℃ for 5 hours for supercritical carbon dioxide drying to prepare the high-silica fiber aerogel felt.

[0055] (3) Density is 130 kg / m³ 3 Basalt fiber felt with a thickness of 3mm and high silica fiber aerogel felt are combined through a sewing process (using 300tex glass fiber untwisted yarn) to finally prepare a fire-resistant double-layer aerogel fiber felt composite material.

[0056] The measured thermal conductivity of the double-layer fiber composite aerogel felt at room temperature is 0.026 W / (m·K), and the tensile strength is 715 N / 25 mm. The tensile strength of the single 5 mm high silica fiber felt before composite is 128 N / 25 mm, and the tensile strength of the 3 mm basalt fiber felt is 121 N / 25 mm.

[0057] A scaled-down model combustion experiment of a bridge cable was conducted on the double-layer fiber composite aerogel felt prepared in Example 1. The aerogel was burned for 1.5 hours under an HC combustion curve to test its heat insulation capacity. The results are as follows: Figure 1 As shown.

[0058] A scaled-down model combustion experiment of a bridge cable was conducted on the double-layer fiber composite aerogel felt prepared in Example 2. It was burned for 1.5 hours under a flame with an HC combustion curve to test its heat insulation capacity. The results are as follows: Figure 2 As shown.

[0059] A combustion experiment was conducted on a scaled-down model of a bridge cable using the double-layer fiber composite aerogel felt prepared in Example 3. The aerogel was burned for 1.5 hours under an HC combustion curve to test its thermal insulation capacity. The results are as follows: Figure 3 As shown in the figure, the prepared double-layer fiber composite aerogel felt exhibits excellent thermal insulation performance.

[0060] Comparative Example 1

[0061] The only difference from Example 1 is that a dual silicon source is not used in the preparation; only tetraethyl orthosilicate is used as the silicon source, and the total molar amount of silicon source remains unchanged.

[0062] The test results showed that the room temperature thermal conductivity of the double-layer fiber composite aerogel felt was 0.027 W / (m·K), and the tensile strength was 553 N / 25 mm. A combustion test was conducted on a scaled-down model of a bridge cable, burning it for 1.5 hours under an HC combustion curve to test its heat insulation capacity. The results are as follows... Figure 4 As shown, with the extension of the fire exposure time, the cable temperature rise rate shows an upward trend, and the protective effect is worse than that of products prepared with dual silicon sources.

[0063] Comparative Example 2

[0064] The only difference from Example 2 is that the two-step aging process is not used; instead, the product is aged in a 1:7 tetraethyl orthosilicate / ethanol mixture for 24 hours.

[0065] The test results showed that the room temperature thermal conductivity of the double-layer fiber composite aerogel felt was 0.031 W / (m·K), and the tensile strength was 925 N / 25 mm. A combustion test was conducted on a scaled-down model of a bridge cable, burning it for 1.5 hours under an HC combustion curve flame to test its heat insulation capacity. The results are as follows... Figure 5 As shown, the aerogel composite material prepared by one-step aging has a higher organic content, resulting in a poorer protective effect compared to the product prepared by two-step aging.

[0066] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A double-layer fiber composite aerogel felt, characterized in that, It is composed of basalt fiber felt and high silica fiber aerogel felt; The high-silica fiber aerogel felt layer is the outer layer, and the basalt fiber felt layer is the inner layer; The high-silica fiber aerogel felt is made of high-silica fiber and aerogel material; The preparation method of the double-layer fiber composite aerogel felt includes the following steps: (1) Preparation of sol: Mix silicon source, anhydrous ethanol and water, add activator to the mixture, adjust the pH of the resulting system to between 2 and 3, and obtain the sol; (2) Preparation of high silica fiber aerogel felt: the high silica fiber was impregnated with the sol, the pH of the system was adjusted to neutral, and after aging, drying and treatment, the high silica fiber aerogel felt was obtained. (3) Preparation of double-layer fiber composite aerogel felt: After the high silica fiber aerogel felt described in step (2) is obtained, the high silica fiber aerogel felt and basalt fiber felt are stacked along the thickness direction, and the two are combined by sewing process using glass fiber untwisted roving with a linear density of 200-300 tex to obtain the double-layer fiber composite aerogel felt. The silicon source is a dual silicon source with a molar ratio of tetraethyl orthosilicate to methyltriethoxysilane of 1:0.8-1; The molar ratio of the silicon source, anhydrous ethanol, and water is 1:15-20:2; The aging temperature is room temperature; the aging steps are as follows: first, aging treatment is carried out in a mixture of tetraethyl orthosilicate and ethanol, followed by a secondary aging treatment in ethanol; the aging temperature for both steps is 60-70℃, and the time for both steps is 12h. The density of the high-silica fiber aerogel felt is 180-200 kg / m³. 3 The thickness is 3-5 mm; the density of the basalt fiber felt is 120-150 kg / m³. 3 The thickness is 3-5mm.

2. The double-layer fiber composite aerogel felt according to claim 1, characterized in that, The activator is hexadecyltrimethylammonium bromide, and the amount added is 0.3-0.5% of the volume of the mixture.

3. The double-layer fiber composite aerogel felt according to claim 1, characterized in that, The volume ratio of tetraethyl orthosilicate to ethanol in the tetraethyl orthosilicate / ethanol mixture is 1:5-7.

4. The application of the double-layer fiber composite aerogel felt as described in claim 1 as a fire-resistant material.

Citation Information

Patent Citations

  • A high-temperature resistant Si-CO aerogel thermal insulation composite material and its preparation method

    CN102276236A

  • High-performance multi-layer thin-mat composite thermal insulation material and manufacturing method thereof

    CN103449777A

  • High-drawing-resistance aerogel composite material and preparation method thereof

    CN113478930A